Education-Based Mobile Apps Platform in Patients Undergoing Surgery: A Systematic Review - Sariati Sariati; Esti Yunitasari; Laily Hidayati (Jurnal Ners, 2020)
Introduction: Providing sufficient information during a pre-operative helps patients understand their condition and plan of care, to identify and manage potential complications, and to reduce hospital readmission. New innovation mobile application platforms put education in the hands of patients and their families. The aim of study was to investigate the effect of mobile application education in patients undergoing surgery.Methods: A systematic review study was based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyzes) with article sources using the Scopus, Science Direct, PubMed and ProQuest databases. Limited to the last 5 years (2015-2020) using English as well as full-text articles. This was done using a combination of keywords and Boolean operators (AND and OR). Keywords used in searching are “Education” “Pre-operative Education”, "Perioperative", "Mobile Application", “Smartphone”, “Multimedia” and "Surgery".Results: Total article found were 438 articles and we just included 15 articles which related to topic. The design RCT was 10 articles, 2 quasi-experimental articles, 1 cohort study, and 2descriptive study. Mobile application platform has multiple benefit and challenges to effective delivery of health information to patients, new models of health care demand patient empowerment and so are fundamentally dependent on success with patient education. Patients indicated they understood of the content prior to discharge.Conclusion: Additionally, patient demonstrated mobile application   advances allow delivery of both individualized and ‘‘just-in-time’’ education. Our findings indicate that education based mobile application platform have a positive effect on patients undergoing surgery.